A hybrid cuckoo search metaheuristic algorithm for solving single machine total weighted tardiness scheduling problems with sequence dependent setup times. (2016) - Marichelvam, M.K.; Geetha, M.
In this paper, we present a hybrid algorithm based on cuckoo search algorithm to solve the single machine total weighted tardiness (SMTWT) scheduling problems with sequence dependent setup times which have been proved to be strongly NP-hard. Three different dispatching rules are incorporated with the initial random solutions of the cuckoo search (CS) algorithm to improve the solution quality. Computational results show that the proposed algorithm is very competitive to many metaheuristic algorithms in the literature.